Parenteral dosage form development and testing of dimethyl trisulfide, as an antidote candidate to combat cyanide intoxication. (17th November 2017) - Kovacs, Kristof; Duke, Anna C.; Shifflet, Marla; Winner, Brittany; Lee, Stephen A.; Rockwood, Gary A.; Petrikovics, Ilona
Abstract: This study focused on the solubility enhancement and the in vivo antidotal efficacy testing of a new potential cyanide (CN) countermeasure, dimethyl trisulfide (DMTS). Various FDA approved cyclodextrins (HPβCD, RMβCD, HPγCD), cosolvents (ethanol, polyethylene glycols, propylene glycol), surfactants (cremophor EL, cremophor RH 40, sodium cholate, sodium deoxycholate, polysorbate 80) and their combinations were applied. Based on the solubility enhancing potential of the tested systems, polysorbate 80 was chosen for further in vivo efficacy studies. A composition comprising 15% polysorbate 80 and 50 mg/ml DMTS with the applied DMTS dose of 100 mg/kg provided a therapeutic antidotal protection of 3.4 × LD50 . For comparison, the present therapy of sodium thiosulfate (TS) with the dose of 100 mg/kg provided only 1.1 × LD50 protection, and at the dose of 200 mg/kg, the LD50 was enhanced by 1.3 times. No difference in the therapeutic protection by DMTS was detected when the concentration of polysorbate 80 was increased to 20% (3.2 × LD50 protection). These data demonstrate the potential importance of DMTS as a CN countermeasure, and the formulation comprising polysorbate 80 provides the base of an injectable intramuscular dosage form that can later serve as a CN antidotal kit suitable for mass scenario.